2016
DOI: 10.1007/s40120-016-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns of Medications for Alzheimer’s Disease in Japan from 2010 to 2015: A Descriptive Pharmacy Claims Database Study

Abstract: IntroductionAlthough four kinds of Alzheimer’s disease (AD) drugs are available at present there was only one drug until 2011 in Japan. This study aimed to elucidate prescription trends of these medications for AD in Japanese outpatients before and after the new drug releases in 2011.MethodsThis descriptive study of pharmacy claims databases analyzed outpatient prescription data from community pharmacies across Japan. The study patients were 20 years or older and first administered medications for AD (donepezi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…These confounders were considered on the basis of the results of previous studies . To examine the effect of the total number of medications, polypharmacy was defined as the prescription of an average of ≥5 non‐AD drugs per month prior to the index month .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These confounders were considered on the basis of the results of previous studies . To examine the effect of the total number of medications, polypharmacy was defined as the prescription of an average of ≥5 non‐AD drugs per month prior to the index month .…”
Section: Methodsmentioning
confidence: 99%
“…Alzheimer's disease (AD) and vascular dementia are the most common causes of EOD . In our previous study involving patients with AD, it was revealed that the proportion of patients with early‐onset AD was approximately 3% amongst all patients in the study population .…”
Section: Introductionmentioning
confidence: 97%
“…We used data obtained from three nationwide pharmacy chains in Japan (Ain Pharmaciez Inc., Kraft Inc., and Nihon Chouzai Co., Ltd.) 7,8) ; the data comprised dispensing records from more than seven million outpatients in 2012, covering approximately 4% of all outpatient dispensations in Japan that year. The patient demographic data are well matched with the entire population of Japan, but pharmacies are typically located in urban areas.…”
Section: Data Sourcementioning
confidence: 99%
“…Indeed, antipsychotics are associated with greater risks for mortality and cerebrovascular events, which has led regulatory agencies to issue warnings or required pharmaceutical companies to add precautions about the use of antipsychotics for people with dementia . However, antipsychotics have still been commonly prescribed in older adults with dementia in Japan and in overseas countries, even after the issue of such warnings or precautions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on the use of antipsychotics in older people with dementia in Japan. Based on analyses of large‐scale medical claims data, the prevalence of antipsychotic use among people prescribed antidementia drugs ranged from 16.8% to 24.9%. These studies limited their study cohort to those prescribed antidementia drugs partly because a diagnosis of dementia in medical claims is not considered reliable.…”
Section: Introductionmentioning
confidence: 99%